Impact Factors of Adult ADHD and Intervention Strategies - Pan, Yue (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Adult Attention Deficit Hyperactivity Disorder (ADHD) is a condition that affects an individual's attention, impulse control and emotional regulation and is one of the most common neurodevelopmental disorders in our society today. It usually develops in childhood, but some patients who are undiagnosed or who do not receive immediate intervention in childhood continue to have the condition into adulthood, exacerbating their pre-existing symptoms. Existing studies tend to focus more on childhood ADHD and less on adult ADHD. According to World Health Organization (WHO) epidemiological survey data, the prevalence of ADHD in adults is between 2.6% and 2.8%. Attention deficit hyperactivity disorder in adults has a significant negative impact on the individual, the family and society. ADHD can make the patient unable to concentrate at school or work, cause some learning difficulties, and cause some stress and anxiety to themselves, as well as increasing the burden on families and society. This study will investigate the characteristics of attention deficit disorder, the factors that influence it, and intervention strategies. It is hoped that the results of this study will improve understanding of attention deficit hyperactivity disorder in adults.